ALTERNATIF PENANGGULANGAN ABRASI DI PANTAI MUARA GEMBONG, BEKASI - Alimuddin, Alimuddin (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2018)
Landuse change in Muara Gembong, Bekasi caused high abrasion. This condition made 3 (three) villages dissapeared,that is Pantai Bahagia, Pantai Mekar and Pantai Sederhana Village. The purpose of this study were to analize abration rate and to assess its mitigation alternatives at coastal area of Muara Gembong, Bekasi.The studywas conducted since July - December 2013. Landsat overlay during 10 years (2003-2012) showed that abrasion in Muara Gembong was 285.635,23 m2. The average of mean sea level change during 10 years (2003-2012) was 0.60 m with the lowest tide was 0.57 m and the highest tide was 0.62 m measured from Mean Sea Level (MSL). Building coastal protection suitable for abrasion problems in the study area is breakwater because breakwater can generate sedimentation in the back of the building and almost no abrasion in other area. Groin can lead to sedimentation in the upstream areas, but the resulting interruption of the sediment supply in downstream side resulting in abrasion while seawall is less effective in hold the sediment transport and shoreline damage to occur end of the building. Based on tidal result analysis the minimum height of coastal wall was 1.19 m